2018
DOI: 10.1103/physrevb.97.075135
|View full text |Cite
|
Sign up to set email alerts
|

Chern-Simons theory and atypical Hall conductivity in the Varma phase

Abstract: In this letter, we analyze the topological response of a fermionic model defined on the Lieb lattice in presence of an electromagnetic field. The tight-binding model is built in terms of three species of spinless fermions and supports a topological Varma phase due to the spontaneous breaking of timereversal symmetry. In the low-energy regime, the emergent effective Hamiltonian coincides with the so-called Duffin-Kemmer-Petiau (DKP) Hamiltonian, which describes relativistic pseudospin-0 quasiparticles. By consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 58 publications
1
21
1
Order By: Relevance
“…We now turn our attention to lifting the energy degeneracy of the p x -and p y -like orbitals at all sites by introducing an asymmetry in the lattice sites [43]. Specifically, we break the four-fold rotational symmetry by increasing the width of artificial-atom sites 1 and 2 in the y-direction by √ 3a (pink arrow in Fig.…”
mentioning
confidence: 99%
“…We now turn our attention to lifting the energy degeneracy of the p x -and p y -like orbitals at all sites by introducing an asymmetry in the lattice sites [43]. Specifically, we break the four-fold rotational symmetry by increasing the width of artificial-atom sites 1 and 2 in the y-direction by √ 3a (pink arrow in Fig.…”
mentioning
confidence: 99%
“…As a first result, in the Section II in Ref. [1], the authors showed that the dynamics of the charge carriers on that Lieb lattice in low-energy regime present a relativisticlike behavior, correctly described by Duffin-Kemmer-Petiau-like hamiltonian (DKP). Disregarding irrelevant constants, this effective hamiltonian is expressed in a simplified version as (see equation (4) in Ref.…”
mentioning
confidence: 93%
“…In an interesting Letter, Menezes et al [1] analized the topological response of a effective bosonic theory defined on the Lieb lattice which is minimally coupled to an external U (1) gauge field in 2 + 1 dimensions. To this purpose, the authors consider a tight-binding hamiltonian with three different species of (pseudo-) gapped fermions (see equations ( 1)-(3) in Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations